Assessment of Language Proficiency and Enhancement Among 1st Phase MBBS Undergraduates - Dharma Rao Vanamali; Himavathy Kodandarao Gara; Abhay Dadaji Hatekar; Jeneeta Baa; Surekha Pardeshi; Naruttam Sonowal; Sarita Panigrahy; Sachin Mulkutkar; Mamata Sar (Assam Journal of Internal Medicine)
Background: Limited language proficiency (LLP) in English and state language may constrain the impetus of a medical undergraduate for effective communication, social interaction, and academic progression. Hence, the study aimed to explore the extent and perceptions pertaining to language barrier among medical undergraduates and to obtain feedback about language and communication skill sessions of foundation course. Materials and Methods: This multi-centric cross-sectional study across five medical colleges in India involved participation of 691 1st phase MBBS undergraduates. The study was conducted in two phases: (a) at the beginning of Foundation course before initiation of language training classes and (b) at the end of training sessions. The questions were either semi-structured or multiple-choice type regarding (a) sociodemographic characteristics, (b) schooling details, and (c) questionnaire regarding proficiency of English and local language and emotional and cognitive responses toward LLP. Results: Out of 691, proficiency for English and respective state language was confirmed by 170 (24.6%) and 318 (46.02%), respectively. Ninety (13.02%) students had no acquaintance for respective state languages. Difficulty in understanding concepts when taught in English and communication breakdown were expressed by 121 (18.22%) and 263 (38.95%) students, respectively. Regarding language and communication skill sessions, improvement in English and state language was expressed by 495 (71.63%) and 521 (75.4%), respectively. The sessions rating was highest for usefulness, followed by quality. Conclusion: Approximately 75% and 50% of MBBS undergraduates of 1st phase expressed LLP for English and state language, respectively, which represents a liability. Language enhancement benefited students in terms of usefulness and better comprehension of medical terminologies and colloquialism. Circumspection of language barrier among medical undergraduates would bridge the gap of linguistic knowledge and communication goal.